The impact of migration on transport and congestion - Tsang, Flavia; Rohr, Charlene (RAND Corporation, 2023)
This study examined evidence on how migration is likely to impact transport networks and congestion. The research was comprised of two phases: a literature review followed by empirical analysis using UK data.